2014
DOI: 10.1002/jobm.201300790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan and oligochitosan on development and mitochondrial function of Rhizopus stolonifer

Abstract: The antifungal activities of chitosan and oligochitosan have been used to control postharvest decay of the fruits. The effect of chitosan and oligochitosan on mycelium growth, spore germination, and mitochondrial function of Rhizopus stolonifer was evaluated in order to establish a connection between fungus development and the main organelle in charge to provide energy to the cell. The mycelium growth of R. stolonifer was significantly reduced on minimum media amended with chitosan or oligochitosan. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The rate of germination rate was > 90% in the non‐treated control after 8 h of incubation in potato dextrose broth at 25 °C, whereas the germination rate of oligochitosan‐treated spores was approximately 50%. These results confirm previous reports demonstrating that oligochitosan inhibited the spore germination of other postharvest fungal pathogens, including A. kikuchiana , P. piricola , M. fructicola , P. expansum and R. stolonifer …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The rate of germination rate was > 90% in the non‐treated control after 8 h of incubation in potato dextrose broth at 25 °C, whereas the germination rate of oligochitosan‐treated spores was approximately 50%. These results confirm previous reports demonstrating that oligochitosan inhibited the spore germination of other postharvest fungal pathogens, including A. kikuchiana , P. piricola , M. fructicola , P. expansum and R. stolonifer …”
Section: Resultssupporting
confidence: 92%
“…Oligochitosan has been suggested as a potential, eco‐friendly alternative to the use of synthetic fungicides for controlling postharvest diseases, and several studies have demonstrated that it can be effective for controlling fungal diseases of plant hosts, including those of economically important horticultural crops . In addition to inducing systemic resistance, oligochitosan has been shown to have a direct inhibitory effect on spore germination, germ tube elongation, and mycelial growth and development of several fungal pathogens, including Alternaria alternata , Alternaria kikuchiana , Physalospora piricola , Monilinia fructicola , Penicillium expansum , Rhizopus stolonifer and Colletotrichum gloeosporioides . A comprehensive understanding of the mode of action by which oligochitosan inhibits fungal pathogens, however, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Control cells and oligochitosan-treated cells showed an increase in the oxygen consumption rate at 12 h. Oligochitosan induced faster consumption of oxygen in the cells incubated for 24 h. After 48 h in culture, oligochitosan induced faster consumption of oxygen by cells, while glycol chitosan provoked slower oxygen consumption. A previous report showed that oligochitosan at 1 mg/mL raised oxygen consumption in Rhizopus stolonifer cells [10]. Therefore, the cells required more energy to repair moderate damages caused by the polymer.…”
Section: Effect Of Chitosan and Its Derivatives On Oxygen Consumptionmentioning
confidence: 94%
“…Cells were weighed, diluted to 50% (w/v) with sterile distilled water, and 50 L (25 mg wet weight) of each suspension was used for the assay. The oxymetric traces were recorded, and the initial oxygen consumption rates were expressed in nmol O 2 min −1 mg −1 [10].…”
Section: Oxygen Consumption Measurement In Treated Cellsmentioning
confidence: 99%
See 1 more Smart Citation